Determination of the optimal shape of matrix elements partitioning on three abstract heterogeneous processors. Issue 1 (1st January 2020) - Klyuyeva, Ye.G; Yavorskij, V.V.; Adamov, A.A.; Utepbergenov, I.T.
Abstract: The paper presents the results of a study done to find the optimal shapes of matrix element partitioning on three abstract heterogeneous processors when performing multiplication operations. An abstract processor model allows applying the research results in systems with different heterogeneous architectures. To determine the optimal partitioning shape, the work uses non-rectangular candidate shapes identified by Ashley DeFlumere in her work as a result of applying the technology of redistribution of matrix elements between the processors «push»: Square Corner, Rectangle Corner, Square Rectangle, Block Rectangle, L-Rectangle, Traditional 1D Rectangular. The optimality of shapes is determined for four classes of matrix multiplication algorithms: Serial Communication with Barrier (SCB), Parallel Communication with Barrier (PCB), Serial Communication with Bulk Overlap (SCO) and Parallel Communication with Overlap (PCO). The Hockney model was used to evaluate the communication complexity of algorithms. Mathematical models of the algorithm execution time were introduced in the paper for each considered candidate shape in all algorithms. Based on the developed mathematical models, software was developed that allows to select the form of elements partitioning between processors, depending on the ratio of their speeds and latency of the transmission medium.